(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Renal cell carcinoma (RCC) and angiomyolipoma (AML) are two of the most frequently presenting renal tumors with very different clinical presentations and treatment approaches. Proper and timely differentiation between the two is essential, given that RCC often needs surgery or systemic therapy and AMLs are usually benign and conservatively treated unless symptomatic. Objective: The main aim of this study was to evaluate and compare the diagnostic performance of ultrasonography and computed tomography (CT) in detecting and differentiating renal cell carcinoma and angiomyolipomas. The study focused on evaluating certain imaging characteristics—like echogenicity, margin features, vascularity (on ultrasound), and enhancement characteristics, calcification, and necrosis (on CT)—and comparing them with histopathological results. Furthermore, the research aimed to measure the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy of each modality so as to establish the most appropriate and feasible imaging device for initial assessment of renal masses in clinical practice. Methods: A cross-sectional analytic survey was carried out on 90 patients between 40–70 years of age at Lahore General Hospital. Both ultrasonography and contrast-enhanced CT scans were performed in all patients, and then confirmed histopathologically. Data were analyzed in SPSS v29 using Chi-square testing to find statistical significance. Results: Ultrasonography had high diagnostic accuracy with sensitivity rates of 91.2% and 87.7% for RCC and AML, respectively, and specificity rates of 78.6% and 71.4%, respectively. PPV and NPV for RCC were 89.6% and 81.4%, and for AML, they were 86.2% and 74%. The overall diagnostic accuracy was 87% for RCC and 85% for AML on ultrasonography. Comparison with CT showed sensitivity and accuracy of 84% and 80% respectively for RCC, and sensitivity and accuracy of 88.8% and 78% respectively for AML. Prominent presenting symptoms were weight loss (88.8%), hematuria (83.3%), and palpable mass (81.1%). Conclusion: Ultrasonography was found to be an extremely sensitive and reliable method for initial diagnosis of RCC and AML for use in routine clinical practice. Still, CT imaging will continue to be necessary in further lesion characterization, particularly with unclear or unusual presentations. It is advised that a combined diagnostic scheme—incorporating imaging, clinical assessment, and histopathological correlation—is utilized to increase diagnostic accuracy and treatment of patients.